ANALYSIS OF DREDGE STABILITY AS CONSEQUENCE OF MODIFICATION FROM ON SHORE TO OFF SHORE OPERATION - JONI WIBOWO(NIM : 13104054); Pembimbing : Dr. Ir. Bagus Budiwantoro, ABAS
The function of dredge in operation is to dredging, transporting, and mooving the materials from deep to surface. Merapin dredge is the property of PT Koba Tin, that operation since 1987 to 2002 for land operation. Because of this dredge will activate in sea operation, so to fulfill this requirement this ship need restoration and modification. But every dredge must be stable and feasible. The initial stability of dredge is influenced by centre of gravity and centre of bouyancy. In this final assignment to analysis the stability, the process separated by two step. (1st) weight and centre of gravity Merapin dredge existing calculation, (2nd) the calculation of merapin dredge modification stability. The result of this analysis showed that Merapin dredge always occured trim in longitudinal direction, from the consequence of change weight and centre of gravity the ladder in operation time. After the weight increase by modification, the result of final freeboard not fulfill the standard. With increasing added pontoon, and good potition arrangement like in 4th design will produce results final freeboard that fulfill the standard. From the calculation, every added pontoon will give load to connection structure around 100 ton. In each added pontoon have 8 connection structure, each other restrain load 12,5 ton. From the results of finite element analysis helped by ANSYS software, maximum of Von-Mises stress is 1,18 x 108 N/m2. This result is safe if compare with allowable stres 2,5 x 108 N/m2, and the safety factor is 2,11.